Viabilitas Probiotik Asal Fermentasi Maggot (Hermetia illucens) terhadap Suhu dan Lama Waktu Penyimpanan: Viability of Probiotics from Fermented Maggot (Hermetia illucens) on Temperature and Storage Time - Fitri, Selma Destiana; Laconi, Erika Budiarti; Martin, Rima Shidqiyya Hidayati; Nahrowi; Utari, Tazkiyah Annisa; Shofiah, Maya; Nugroho, J E; Rinaldy, A; Erlangga, K (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
This study aimed to analyze the viability of probiotics from maggot fermentation under environmental influence i.e., temperature and storage time. The experimental design was a factorial completely randomized design (CRD) using storage time and temperature as factors with 4 replications. The storage time was 3 months with monthly observations while the storage temperatures observed were 4°C, 28°C, 38°C and 48°C. The parameters were physical quality, microbial population, total titrated acid (TTA), and antimicrobial activity. The results showed that probiotics from maggot fermentation were dominated by lactic acid bacteria. The pH of probiotics increased and physical quality changes occured during storage. The yeast and actinomycete populations were not found during month 2 and month 3, respectively, while the population of Bacillus sp. decreased. There was an interaction between storage time and temperature on the population of lactic acid bacteria and TTA. Another interaction was found in the antimicrobial activity produced by probiotics/antibiotics and storage temperature in the third month of storage. Storage time and temperature influenced the physical quality of probiotics, the population of lactic acid bacteria and TTA, while the inhibition zone was influenced by the probiotic/antibiotic solution and storage temperature. It can be concluded that the highest viability of fermented maggot probiotics (LAB) was obtained in the 1st month at a temperature of 38℃. Key words: maggot fermentation, probiotics, storage time, temperature, viability